2016
DOI: 10.1590/s0080-623420160000100011
|View full text |Cite
|
Sign up to set email alerts
|

Social representation of Alzheimer's disease for family caregivers: stressful and rewarding

Abstract: Objective:To understand the content of Social Representation (SR) of family caregivers of Alzheimer's disease patients. Method: Interviews were conducted with 26 caregivers and analyzed by the ALCESTE software. Results: The SR content was structured in two thematic axes called Daily Life and Care and Medical and Emotional Concepts and Outcomes. The first axis creates images related to the routine of interaction with the sick person, and contains a description of care procedures, experiences, and practices appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
1
3
0
14
Order By: Relevance
“…O IS sublinhou a natureza simbólica da vida social, sendo a concepção dos atores a respeito do mundo social que constitui o objeto essencial da pesquisa sociológica (19)(20) . Esse referencial teórico está centrado na natureza social.…”
Section: Métodounclassified
“…O IS sublinhou a natureza simbólica da vida social, sendo a concepção dos atores a respeito do mundo social que constitui o objeto essencial da pesquisa sociológica (19)(20) . Esse referencial teórico está centrado na natureza social.…”
Section: Métodounclassified
“…O diagnóstico de Alzheimer ocasiona um abalo na relação intrafamiliar, podendo resultar em emoções negativas (Vizzachi et al, 2015). A aflição e o medo que o diagnóstico de Alzheimer traz para a relação, faz com que a família apresente um sentimento de luto, considerando o diagnóstico como uma ameaça para a identidade do idoso ( Folle, Shimizu & Naves, 2016).…”
Section: Introductionunclassified
“…O ambiente familiar/doméstico é transformado tendo como objetivo o acolhimento integral do familiar/idoso que, agora, necessita de cuidados para exercer suas atividades diárias, o que demostra um abatimento biopsicossocial no cuidador, visto que o mesmo, exerce, quase que exclusivamente, o cuidado direcionado ao idoso (Folle et al, 2016). A pesquisa tem como objetivo compreender a forma como ocorre a reorganização e reestruturação da dinâmica intrafamiliar em relação a Doença de Alzheimer, visto que o desconhecimento da mesma assume o caráter de luto.…”
Section: Introductionunclassified
“…Studies have demonstrated the social impact on the health and well-being of formal and informal caregivers 5,9,10 . It is they who immediately and directly suffer the negative consequences of having to deal with a relative with Alzheimer's disease 11 .…”
Section: Introductionmentioning
confidence: 99%